INSILICO DOCKING ANALYSIS OF CARBAZOLE ALKALOIDS FROM MURRAYA KOENIGII AGAINST PP2A - Dr.R.MANIMEKALAI,; M.VICTORIYA SALOMI,; G.SHOBA, (International Journal of Pharma and Bio Sciences, 2015)
Carbazole alkaloids constitute an important class of naturally occurring heterocycles, isolated from the Rutaceae family. Carbazole alkaloids were isolated as natural products from Murraya koenigii that exhibited strong pharmacological activity. This study is a novel approach emphasizing the significance of natural products like carbazole alkaloids as a prime solution to unanswered questions like the treatment of Alzheimer’s disease. Tau hyper-phosphorylation is thought to play an important role in the etiology of Alzheimer’s disease (or AD) by facilitating the formation of neurofibrillary tangles. The ideal way to reduce the hyperphosphorylation is to enhance the activity of the principal phospho-tau phosphatase, phosphoprotein phosphatase 2A (PP2A). The 3D structure of phosphoprotein phosphatase 2A is subjected to Molecular Docking with carbazole alkaloids from Murraya koenigii. Docking scores indicates the application of carbazole alkaloids as Potential and Natural Therapeutic agents to combat Alzheimer’s disease.Keywords: Alzheimer’s disease, Carbazole alkaloids, Murraya koenigii, Molecular docking, PP2A